Tolerância à salinidade e respostas espectrais foliares em mudas de quatro espécies ornamentais herbáceas tropicais - Oliveira, Adriana Cruz de (2022)
In the Brazilian semiarid region, especially in times of water scarcity, it is common the use brackish water to irrigate crops. It is known that the use of low-quality or brackish water affects the development of most crops. Many studies on the effects of brackish water irrigation on crop salt-tolerance focus on grasses and legumes of economic importance, while studies on the same subject applied to ornamental species are still scarce. In ornamental species, it is important to assess tolerance under both quantitative and qualitative aspects, focusing mainly on products intended for commercialization. Therefore, the objective of the present work was to evaluate the salinity tolerance and foliar spectral responses of tropical herbaceous ornamental species, in the initial growth stage and production of seedlings for commercialization. The experiment was carried out in the experimental area of the Agrometeorological Station of the Federal University of Ceará -UFC, in a protected environment. The experimental design used was randomized blocks, in a split-plot scheme, with the plots composed of five irrigation-water salinity levels - ECw (0.5; 2.0; 4.0; 6.0 and 8.0 dS.m-1), and the subplots by four ornamental herbaceous species: Catharanthus roseus, Celosia cristata, Celosia plumosa and Chrysanthemum coronarium, each with four replications. The following measurements were performed: plant growth, spectral responses, chemical analysis of leaves, visual quality of plants, salt tolerance, and leaf spectral responses. The growth and physiological responses of all species were negatively affected by salinity. The results indicated that the species Chrysanthemum coronarium had the lowest ability to develop with salinity irrigation above 2.0 dS.m-1 with survival of only 25% of the plants in salinity of 4.0 dS.m-1. On the other hand, Celosia plumosa showed good potential for development under irrigation with water up to 4.0 dS.m-1, showing the highest survival rates at the highest salinity levels. The visual quality of the plants was maintained up to 2.0 dS.m-1 for the species C. coronarium and 4.0 dS.m-1 for the species C. cristata, C. plumosa and C. roseus, even with moderate reductions in the production of biomass. The species C. cristata, C. plumosa and C. roseus were spectrally differentiable. The spectral responses of the saline treatments, however, did not show notable differences, except for the level of 8.0 dS.m-1.